Jamu brand Indonesia: consumer preferences and segmentation - Prabawani, Bulan (Archives of Business Research, 2017)
Indonesia is one of the countries that develop traditional herbal medicine, which is called Jamu. However, Jamu is consumed by the poor. Meanwhile, the rich prefer to use modern health treatment. In addition, there is no sufficient confident of people to consume Jamu as their main medical treatment. Hence, identification of potential consumer of Jamu from demographic characteristics and exploration of consumer preferences of Jamu according to the market segments in Indonesia is important for herbal medicine industry to develop a consumer-based marketing strategy. Cramer’s V-test statistical test was used for the analysis of 183 data survey. The findings are consumers of Jamu assumed that Jamu is cheap, easy to obtain, have no side effects, natural, and safe to be consumed. But, they considered herbs as an alternative medicine or therapy, and even as the last resort. Jamu is potential to be developed by product and pricing differentiation, and packaged as a product that emphasizes value with halal certification. In addition, the classification of Jamu as Phytopharmacy has not affected consumer purchasing decisions as it has not been included in the health care system. For middle up segments, Jamu needs a strong brand using English language and required medical professionals as an advisor.